2006
DOI: 10.1175/waf931.1
|View full text |Cite
|
Sign up to set email alerts
|

Severe Convective Wind Environments

Abstract: Nontornadic thunderstorm winds from long-lived, widespread convective windstorms can have a tremendous impact on human lives and property. To examine environments that support damaging wind producing convection, sounding parameters from Rapid Update Cycle model analyses (at 3-hourly intervals) from 2003 were compared with 7055 reports of damaging winds and 377 081 occurrences of lightning. Groundrelative wind velocity was the most effective at discriminating between damaging and nondamaging wind convective env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…This is an important point, since the effects of the mean wind and its orientation relative to the cold pool are underemphasized aspects of forecasting the strength and structure of quasi-linear MCSs (Evans and Doswell 2001, Corfidi 2003, Parker and Johnson 2004, Kuchera and Parker 2006. Although the MCS motion vector is not an exact analog to the motion of the cold pool, this section examines various properties of the inflowing environment relative to the MCS motion vector to see if these may be used as an indicator of the potential severity of the system and to gain further insight into the propagation characteristics of MCSs.…”
Section: ) Ground-relative Mean Windsmentioning
confidence: 99%
“…This is an important point, since the effects of the mean wind and its orientation relative to the cold pool are underemphasized aspects of forecasting the strength and structure of quasi-linear MCSs (Evans and Doswell 2001, Corfidi 2003, Parker and Johnson 2004, Kuchera and Parker 2006. Although the MCS motion vector is not an exact analog to the motion of the cold pool, this section examines various properties of the inflowing environment relative to the MCS motion vector to see if these may be used as an indicator of the potential severity of the system and to gain further insight into the propagation characteristics of MCSs.…”
Section: ) Ground-relative Mean Windsmentioning
confidence: 99%
“…Indeed, some examples (e.g., Maddox 1980;Trier and Parsons 1993) reveal that the passage of an elevated MCS may be marked by minimal changes in the surface temperature. Even so, at least a subset of MCSs are known to produce severe winds at night and on the cold side of fronts (e.g., Johns and Hirt 1987;Kuchera and Parker 2006). One possibility is that such systems are still cold pool driven and surface based, despite their comparatively stable boundary layers.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the CAPE and DCAPE over Taizhou at 16:00 LST 18 March 2014 is about 0 and 300 J·kg −1 respectively which means both the convection at low-level and dry intrusion from upper-level are weak. As documented by many studies [23,24], large quantity of energy is needed for the development of severe convective systems. CAPE and DCAPE which are two energy indices are usually used for measuring the energy related to convective systems.…”
Section: Case Ii: Hailstorm Eventmentioning
confidence: 99%